2020
DOI: 10.4235/agmr.20.0020
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Evaluation of the Sarcopenia Quality of Life (SarQoL) Questionnaire: Translation and Validation of its Psychometric Properties

Abstract: Sarcopenia is a progressive and generalized loss of muscle mass and function with advancing age. 1,2) This geriatric syndrome is now considered an increasing public health issue worldwide. 3) Sarcopenia is associated with adverse health outcomes such as physical impairment, mobility limitations, increased fall risk, hospitalization, and mortality. 4) In the last decade, several sarcopenia definitions and proposals for diagnostic criteria have been published. Among these, the revised consensus criteria of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The SARCPH study showed a decrease in QoL areas, especially physical functions, among sarcopenic patients [23].In one study, mean SarQoL scores were reported as 58.43±17.13 for Sarcopenic patients and 69.89±13.31 for non-sarcopenic patients [24]. In our study, the mean SarQol total value during the pandemic period was found to be 66.91 ± 14.35. programmes [25].…”
Section: Discussionsupporting
confidence: 47%
“…The SARCPH study showed a decrease in QoL areas, especially physical functions, among sarcopenic patients [23].In one study, mean SarQoL scores were reported as 58.43±17.13 for Sarcopenic patients and 69.89±13.31 for non-sarcopenic patients [24]. In our study, the mean SarQol total value during the pandemic period was found to be 66.91 ± 14.35. programmes [25].…”
Section: Discussionsupporting
confidence: 47%
“…Copyright © 2021 Wolters Kluwer Health, Inc. All rights reserved. sarcopenia diagnosis in some sarcopenia studies including a recent study that validated Ukrainian version of Sar-QoL scale [29].…”
Section: Ishii Testmentioning
confidence: 99%
“…It perhaps needs to be emphasized that at the time of the conception of the SarQoL questionnaire by Beaudart et al, the EWGSOP definition was in use [ 24 , 47 ]. The EWGSOP2 definition for sarcopenia was published in 2019, all SarQoL studies executed thereafter chose to use this updated definition to define sarcopenia in their study population with the exception of Le at al who used the AWGS 2019 definition [ 34 , 39 , 41 , 43 , 48 ].…”
Section: Resultsmentioning
confidence: 99%